Interpersonal Communication Of Madrasah Aliyah Teachers In Overcoming Students’ Anxiety In Facing University Entrance Selection - Lubis, Sallima Zarli; Nurhanifah, Nurhanifah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Teachers' interpersonal communication plays an important role in guiding madrasah students to face the pressure of college selection by reducing anxiety through constructive, ethical, supportive, and emotional interactions. This research aims to formulate a systematic and contextual approach to understand the role of teachers' interpersonal communication in overcoming the anxiety of madrasah students facing college selection. This study uses a qualitative approach of case studies with data collection techniques through interviews, observations, documentation, purposive selection of informants, data analysis, data condensation, categorization, theme drawing, and validation through triangulation and member check. The results showed that teachers used linear, interactive, and transactional communication models as well as verbal, nonverbal, and Islamic communication value strategies to help students manage anxiety in facing public university selection. There are collaborative efforts, such as communication with parents, self-motivation, and information searching, as well as obstacles in the form of bad moods and incompatibility of academic choices with students' abilities. Conclusions: transactional communication, verbal-nonverbal strategies, Islamic principles, and religious practices effectively manage students' anxiety through dynamic dialogue, collaborative approaches, and personalized communication in an Islamic educational environment.